2023
DOI: 10.3390/ijms24076438
|View full text |Cite
|
Sign up to set email alerts
|

A Leucine-Rich Repeat Receptor-like Kinase TaBIR1 Contributes to Wheat Resistance against Puccinia striiformis f. sp. tritici

Abstract: Plant cell surface-localized receptor-like kinases (RLKs) recognize invading pathogens and transduce the immune signals inside host cells, subsequently triggering immune responses to fight off pathogen invasion. Nonetheless, our understanding of the role of RLKs in wheat resistance to the biotrophic fungus Puccinia striiformis f. sp. tritici (Pst) remains limited. During the differentially expressed genes in Pst infected wheat leaves, a Leucine-repeat receptor-like kinase (LRR-RLK) gene TaBIR1 was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…A previous study showed that TuRLK1 is required for the immune response to stripe rust mediated by the NLR protein YrU1, and may also play an important role in resistance to other pathogens such as powdery mildew, where the expression of the leucine-rich repetitive receptor-like kinase TuRLK1 is upregulated in wheat infected with Pst CYR33 [ 48 ]. In addition, the leucine repeat receptor-like kinase (LRR-RLK) gene TaBIR1 , a cell-surface RLK, is suggested to contribute to wheat stripe rust resistance, and may act as a positive regulator of plant immunity in a BAK1-dependent manner [ 49 ]. Receptor-like kinase genes have a crucial role in stripe rust resistance in Wheat High-temperature seedling plant (HTSP) resistance, and Wang et al [ 50 ] have shown that TaXa21 is an RLK related to TaWRKY76 and TaWRKY62 and acts as a positive regulator of Pst resistance in wheat HTSP resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that TuRLK1 is required for the immune response to stripe rust mediated by the NLR protein YrU1, and may also play an important role in resistance to other pathogens such as powdery mildew, where the expression of the leucine-rich repetitive receptor-like kinase TuRLK1 is upregulated in wheat infected with Pst CYR33 [ 48 ]. In addition, the leucine repeat receptor-like kinase (LRR-RLK) gene TaBIR1 , a cell-surface RLK, is suggested to contribute to wheat stripe rust resistance, and may act as a positive regulator of plant immunity in a BAK1-dependent manner [ 49 ]. Receptor-like kinase genes have a crucial role in stripe rust resistance in Wheat High-temperature seedling plant (HTSP) resistance, and Wang et al [ 50 ] have shown that TaXa21 is an RLK related to TaWRKY76 and TaWRKY62 and acts as a positive regulator of Pst resistance in wheat HTSP resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study identified an RLK family number, namely TaBIR1, contributing to wheat resistance against the fungus Puccinia striiformis f. sp. tritici [20]. Another study reported several RLKs as candidate R genes against anthracnose in common beans [21,22].…”
Section: Introductionmentioning
confidence: 99%